Strategy to Manage the Interplay Between Multiple Concurrent Digital Transformation Initiatives in the Financial Services Sector - Mishra, Abhishek (Global journal of Business and Integral Security, 2025)
This dissertation delves into the intricate aspects of digital transformation within the financial services sector. It focuses on the integration of current processes, technology, human resources, and organisational culture in implementing multiple concurrent digital initiatives. Five pivotal questions guide the research: How do organisational strategies align with client expectations? What are the prevailing trends and challenges? How can we assess digital maturity levels across the sector? And can machine learning models predict the success and scope of digital initiatives based on organisational features? Key findings from the study revealed that large, resource-rich financial institutions are better equipped to manage multiple digital transformation efforts effectively. In contrast, smaller firms and those in various geographical locations face significant challenges due to resource constraints and less formalized processes. The study emphasizes that client expectations, increasingly centered on innovative, reliable, and personalized digital services, are a driving force for financial organisations to align their digital strategies. This alignment is crucial to enhance client satisfaction and remain competitive. Emerging technologies such as artificial intelligence and blockchain are acknowledged as pivotal in driving transformation, yet many firms exhibit a readiness gap that impedes effective adoption and integration. The study also highlighted substantial gaps in digital strategies, particularly in integrating legacy systems, meeting regulatory compliance, and promoting sustainable practices. The research successfully demonstrated that it is possible to predict the number of digital initiatives an organisation will undertake based on specific organisational characteristics through the development and application of machine learning models. This predictive capability provides valuable insights for strategic planning and helps firms benchmark their progress against industry standards. The dissertation concludes that financial services firms must adopt a holistic approach that integrates technology with strategic business goals and that clients need to thrive in a digital-first world. Effective digital transformation requires technological uptake, cultural adaptability, and robust management strategies to navigate the complexities of digital integration. In essence, this research provides a comprehensive analysis of the digital transformation landscape within the financial services sector, offering critical insights and strategic recommendations that can guide organisations in their digital journey, fostering innovation, operational efficiency, and enhanced customer engagement in a dynamically evolving industry landscape.